Construction of the Argument for the Decision of the Jambi District Court No. 18/Pid.Sus-TPK/2023/PN Jmb - Ardinah, Ardinah; Prihadi, Prihadi; Efendi, Anwar; Hartono, Hartono (JOLLT Journal of Languages and Language Teaching, 2024)
Indonesia has imposed penalties for criminal acts of corruption by sentencing defendants to additional crimes, in addition to the main crime through court decisions. As a text, a court decision is also a practice that uses language like any other text. Therefore, it cannot be denied to analyze the text using the field of forensic linguistic studies. This research aims to explore the argumentative structure of court decisions regarding criminal acts of corruption and additional crimes as argumentative texts. In his analysis, all legal considerations become the basis for decision making. The data in this research is the text of the Jambi District Court decision no. 18/Pid.Sus-TPK/2023/PN Jmb using a qualitative descriptive method referring to a forensic linguistic approach. The results of this research include several things, namely the panel of judges used an indictment that had a high level of empathy and focalization because the indictment was obtained from interviews with the defendants. Thus, it can be concluded that because the claims of ’legitimate and convincing’ and ’committing criminal acts of corruption together’ are met argumentatively. However, the claim of ’subjected to criminal acts of corruption and additional crimes’ needs to be questioned. This is because the six defendants had different sentences. In fact, in the indictment the detailed amount of money received is stated, so this claim is problematic from an argumentative theory perspective.